The Impact of Private Investment and Social Investment in the Education Sector in Indonesia - Sarung Allo, Leticya; Hasibuan, Friska Shinta Dame (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2024)
Investment in the field of education stands as the foremost investment in a nation's development. Through education, the skills and productivity of the workforce are enhanced, highlighting the profound impact of educational development on national progress. Nevertheless, the current quality of education in Indonesia remains disparate due to uneven developmental efforts. In light of this situation, private investors are presented with an opportunity to invest in education and facilitate its administration. This research aims to scrutinize the impact of private investor presence and social investment in the educational domain. The research methodology employed is a literature review, examining various sources addressing private investment, social investment, and education. Findings reveal that the involvement of private investors yields positive effects, including enhanced educational quality, increased financial resources, curriculum development innovation, and long-term benefits such as improved employment and health outcomes. However, the presence of private investors also brings negative repercussions, notably in the form of educational access disparities. Impoverished communities face challenges in accessing education in relatively expensive private schools. To mitigate these adverse effects, companies engage in Corporate Social Responsibility (CSR) initiatives in education, particularly in regions where equal access to education remains crucial. This study serves as a reference for contemplating policies involving private investors in educational development within specific areas.